COVID-19: Tra diritti umani e prospettive sociali (Società e diritti, 2021)
AbstractThe article focuses on some concepts related to the Covid-19 pandemic: stigma, freedom, poverty, human rights and resilience. The pandemic has forced us to reshape our lives and the effects on our future are yet to be fully understood. The many examples of solidarity and self-denial have unfortunately also highlighted some macro and micro-differentiations: fragile and vulnerable groups such as women, immigrants, people with disabilities, etc., have seen an increase in the processes of stigmatization, exclusion and marginalization with serious consequences on their lives. In this regard, the text cites the alarming data of Amnesty International which calls for respect for human dignity and human rights for all persons. A respectful response to any health emergency is given by the highest possible level of balance between the maintenance of human rights, as enshrined in the Universal Declaration of Human Rights, and the protection of public health. Restrictions on freedom of movement, association, etc. must necessarily be established by law and be proportionate to the achievement of a legitimate goal. Every human right is in close correlation with the others and the protection of one guarantees the enjoyment of the others, including the right to health. The future challenge for the entire social and health system, and for the professionals who work there, is the organization of care and treatments that are ever closer to the citizen-patient territory with the active involvement of the entire formal and informal network, developing new forms of proximity and activating resilience processes. The reduction of marginalization, exclusion and socio-economic poverty is an issue that affects everyone.